Problemy doboru zmiennych w zagadnieniach grupowania obiektów metoda FeatureSelector heurystycznego doboru cech - Lasek, Mirosława (Feature Selection in Clustering - Application of the Feature Selector Heuristic Method, 2005)
The aim of this paper is to discuss problems concerning feature selection for grouping objects and to propose heuristic method for determining such features which can discriminate objects as best as possible. In the proposed method we start with single feature to which next features are added until obtaining such good possibilities of clustering with assumed criteria of quality, so that no further improvement of quality of clustering is possible. In the paper, algorithm of the method has been described, the strengths and weaknesses of the algorithm are examined and discussed. The method is illustrated with an example of feature selection for clustering of industrial enterprises in order to analyse and compare their financial standing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 87-95